Techniques for effective communication - Pace, R. Wayne; Peterson, Brent D.; Burnett, M. Dallas (Massachusetts : Addision-Wesley Publishing Company, 1979)
This is a book about communication. It has been written to help you do better the thing that you do most. No human activity is so constant, pervasive, and important as the act of communicating.
1. The idea of communication techniques -- 2. Dyadic communication -- 3. Small group communication -- 4. Audience communication -- 5. Another look at the idea of communication techniques.
Keywords: COMMUNICATION